Comprehensive Protocol for the Identification and Characterization of New Psychoactive Substances in the Service of Law Enforcement Agencies - Bulska, Ewa; Bachliński, Robert; Cyrański, Michał K.; Michalska-Kacymirow, Magdalena; Kośnik, Wioletta; Małecki, Paweł; Grela, Karol; Dobrowolski, Michał A. (Frontiers in Chemistry, 2020)
A non-routine, comprehensive protocol for characterization of emerging new psychoactive substances (NPS) including chemical structures, impurities, as well as crystal structures, has been developed to facilitate the work of law enforcement agencies. A set of NPS have been synthesized, identified and characterized by various analytical methods in order to be used as certified reference standards (CRMs). Seven selected compounds (5-IT, NM-2201, MT-45, AB-CHMINACA, UR-144, 5F-PB-22 and 4-CMC) were synthesized on the laboratory scale, then the process was upscaled to semi-technical. All products were analyzed by electrospray Q/TOF-MS/MS for molecular structure identification. The presence of by-products, as well as metal impurities, arising from the performed syntheses were characterized by reversed phase liquid chromatography (RP-HPLC) with DAD and Q/TOF-MS detection and inductively-coupled plasma with quadrupole mass spectrometer (ICP-QMS), respectively. Additionally, the crystal structures of UR-144, NM-2201, 5F-PB-22 and 4-CMC have been determined by single-crystal and powder X-ray diffraction.